Pelatihan pembuatan kue serabi aneka rasa pada ibu rumah tangga di Kabupaten Bantaeng - Ratnawati Tawani; Syamsidah Syamsidah (DEDIKASI, 2019)
This training aims to: 1) be more skilled in the world of catering 2) develop the potential that is already owned for its own and commercial uses independently. 3) increase productivity with catering and business activities. The training on empowering housewives through training in making pancakes of various flavors in Bantaeng Regency is a partnership program to the community as a solution to the problem of less productive housewives in Bantaeng Regency. The target audience for the training was 15 housewives in Bantaeng Regency. The training method is done in the form of lectures, questions and answers, discussions and practices. After conducting training to housewives through making pancakes of various flavors in Bantaeng Regency, it can be concluded that as many as 15 trainees have understood and understood well how to make various flavors of pancake cakes directly, both for themselves and others. The trainees not only were skilled in making pancakes of various flavors, production methods and marketing techniques also provided inspiration for the importance of empowering housewives through continuous catering training.